Improvement of special physical preparation of athletes 9–10 years old engaged in rhythmic gymnastics - Дейнеко, Альфія; Красова, Інна (Slobozhanskyi Herald of Science and Sport, 2018)
Alfiya Deyneko & Inna Krasova Purpose: to substantiate the effectiveness of using the author's methodology for improving the special physical training of athletes 9–10 years old engaged in artistic gymnastics. Material & Methods: in the study, during the year, took part 16 athletes 9–10 years old, engaged in rhythmic gymnastics. To identify the effectiveness of the author's methodology, analysis and generalization of literary sources, pedagogical observation, testing, pedagogical experiment, methods of mathematical statistics. Results: based on the results of the experiment, the improvement of practically all the studied indicators was revealed, namely, the results of the implementation of equilibrium varieties (15–39%) and jumps (20–42%) were significantly improved. Conclusions: the obtained results showed the effectiveness of the developed author's methodology aimed at improving the special physical training of athletes during the preliminary basic training.